POLITIK PANGAN BERBASIS INDUSTRI TEPUNG KOMPOSIT (Forum Penelitian Agro Ekonomi, 2020)
Total Indonesian population of 250 million people leads to some crucial problems in provision and management of staple food. Main sources of staple food are cereal, mainly rice. Another important source of carbohydrate is imported wheat flour and it discourages national food security. Meanwhile, as a tropical country, Indonesia has many sources of carbohydrates (food crops) such as tuber crops (cassava, sweet potatoes), cereals (corn), and palm (sago) potentially replace partially or entirely the consumption of rice and wheat flour. This paper discusses the food politics within the perspective of food security based on composite flours as substitution or replacement of wheat flour. Natural growth of local commodity based on flour industry is very slow and it needs some efforts and policies on its acceleration. It suggests some policy recommendations on how to strengthen and accelerate composite flour industries. Required policy includes assistance, value-added tax relief, and promotion. Value-added tax paid by the government is considered as an incentive to wheat importers and flour industry to develop composite flour.
Keywords: food politics; local food products; composite flour; food security